Exposure of ciprofloxacin-resistant Escherichia coli broiler isolates to subinhibitory concentrations of a quaternary ammonium compound does not increase antibiotic resistance gene transfer. (16th April 2019) - Maertens, H; De Reu, K; Meyer, E; Van Weyenberg, S; Dewulf, J; Van Coillie, E
ABSTRACT: Resistance to antibiotics threatens to become a worldwide health problem. An important attributing phenomenon in this context is that pathogens can acquire antibiotic resistance genes through conjugative transfer of plasmids. To prevent bacterial infections in agricultural settings, the use of veterinary hygiene products, such as disinfectants, has gained popularity and questions have been raised about their contribution to such spreading of antibiotic resistance. Therefore, this study investigated the effect of subinhibitory concentrations of benzalkoniumchloride (BKC), a quaternary ammonium compound (QAC), on the conjugative transfer of antibiotic resistance genes. Five Escherichia coli field strains originating from broiler chickens and with known transferable plasmid-mediated ciprofloxacin resistance were exposed to subinhibitory BKC concentrations: 1/3, 1/10 and 1/30 of the minimum bactericidal concentration. Antibiotic resistance transfer was assessed by liquid mating for 4 h at 25°C using E. coli K12 MG1655 as recipient strain. The transfer ratio was calculated as the number of transconjugants divided by the number of recipients. Without exposure to BKC, the strains showed a ciprofloxacin resistance transfer ratio ranging from 10 −4 to 10 −7 . No significant effect of exposure to subinhibitory concentrations of BKC was observed on this transfer ratio.